Some Measures to Manage the Quality of Training Programs According to AUN-QA Standards at the Faculty of Education, Saigon University - Nguyen Huy Dung (RIRAI Publisher, 2024)
In the context of globalization, countries not only compete in the fields of economics, science and technology, goods and services but also compete in the quality of education. In 2016, the AUN organization’s set of educational evaluation standards version 2.0 was launched, helping educational institutions in Southeast Asia in general and Vietnam in particular to improve and enhance the quality of education in a prompt sustainable way. The set of standards has been improved in Version 4.0 issued in 2022. Saigon University is a public university that has focused on improving the quality of education through applying the standards and criteria of the AUN-QA model to the quality management of training programs. In this article, we want to find optimal measures to improve the quality of training programs according to AUN-QA standards at the Faculty of Education, Saigon University to meet the needs of society.